Social Personality Of Upi Social Studies Students After Entering The Merdeka Campus Program - Kirani Kirani; Sapriya Sapriya; Jupri Jupri (Jurnal Mirai Management, 2023)
There are various forms of social personality based on the opinion of Carl Rogers, then arranged systematically in this study which has a focus on three aspects of social personality attitudes, namely leadership, tolerance, and empathy. All three are related to the social competence of social studies teachers who have an urgency to develop a social personality, especially for students so that later they can adapt in the school and community environment even though they have different backgrounds and can become professional social studies teachers in the future. The approach used in this study is a qualitative approach and case study method, so the data collected comes from research results by conducting observations, interviews, and documentation. The researcher analyzed the social personality conditions of UPI 2019 IPS Education Teaching Campus students which are related to the social competence of IPS teachers after participating in the Teaching Campus program with service placements who have different cultural backgrounds. The social personality of UPI 2019 IPS Education students after participating in the Teaching Campus program at a service center that has a different cultural background has appeared in three aspects of attitude, namely leadership, tolerance, and empathy so that students are able to adapt. In addition, there is a link between social personality and the social competence of social studies teachers so that students are equipped to become prospective professional social studies teachers. The results of this research are used as material in the field of education to continue to provide innovation on the sustainability of the Merdeka Campus program, especially the Teaching Campus so that students born from the program are able to spread benefits more broadly with higher quality social personality attitudes. Kata Kunci: Merdeka Campus Program; Social Personality; Social Competence of Social Studies Teacher